Bung Karno masalah pertahanan-keamanan - Soekarno, 1901-1970 (Penerbit PT. Gramedia Widiasarana Indonesia bekerjasama dengan Founding Father House, 2010)
On defense and security in Indonesia during Sukarno's administration; collection of speeches.